Comparative fattening performance of two types of cattle in Ethiopia - Jepsen, O.; Creek, M.J. (1976)
An input/out put feeding trail was conducted to compare the performance of Boran and Arsi cattle, in cattle, in Ethiopia. The cattle were introduced to feed a high molasses ration 48.5% DM, Noug seed cake 21.7% DM, Maize grain 8.6% DM, eragrostis hay 20% DM, and minerals 1.2% DM both zebu types on the feedlot were slaughtered at 73, 101, 129 and 157 days of feeding trail after splitting into uniform groups. There are 4 cattle groups per each zebu type containing 10 and 8 cattle for Boran and Arsi respectively. Over the whole feeding periods the average daily gain and dressing percentage ranges from 554 to 613 grams and 48.1% to 52.9%, and 778 to 893 grams and 47.9 to 54.5% for Arsi and Boran respectively. The Boran is significantly different and superior from Arsi interims daily gain and dressing percentage. However because of the lower feed intake of the Arsi their live weight gain response to feed input is very similar to that of Boran. The conversion ratio, a kg feed DM used to produce one kg of edible tissue were 16.75 and 17.04 for Arsi and Boran, respectively. This result showed that both types of zebu cattle would be highly effective converters of feed into edible beef.